Is zoonotic Plasmodium vivax malaria an obstacle for disease elimination? - Bárbara Aparecida Chaves; Denise Anete Madureira de Alvarenga; Matheus de Oliveira Costa Pereira; Marcelo Gordo; Emanuelle L. Da Silva; Edson Rodrigues Costa; Aline Souza de Menezes Medeiros; Igor José Martins Pedrosa; Daniela Brito; Maurício Teixeira Lima; Maria Paula Mourão; Wuelton M. Monteiro; et al. (Malaria Journal, 2022)
Abstract Background The groundwork for malaria elimination does not currently consider the potential of Plasmodium zoonotic cycles that involve non-human primates (NHPs) in sylvatic environments. Since vivax malaria is less responsive to control measures, finding Plasmodium vivax infected NHPs adds even more concern. Methods Both Free-living monkeys in forest fragments inside the urban area and captive monkeys from a local zoo had blood samples tested for Plasmodium species. Results In this study, among the Neotropical monkeys tested, three (4.4%), one captive and two free-living, were found to be naturally infected by P. vivax. Conclusion This important finding indicates that it is necessary to estimate the extent to which P. vivax NHP infection contributes to the maintenance of malaria transmission to humans. Therefore, the discussion on wildlife conservation and management must be incorporated into the malaria elimination agenda.